The linkage between performance of healthcare professionals and management practices in health care organizations - Munaza Bibi (Journal of the Pakistan Medical Association, 2021)
Abstract The performance of healthcare professionals is now become a great apprehension for health care organizations to deliver quality services. So, organizations nowadays considering management practices to effectively manage their human resource as they are an essential resource to deliver services through their performance. Besides, the objective of the current paper was to describe the link between management practices and the performance of healthcare professionals in healthcare setup. In addition, based on review it has been found that recruitment & selection, training & development, performance appraisal along with compensation, practices of health and safety as well as flexible working hours play a crucial role in the enhancement of employee performance whereas ineffective execution of these practices has negative influence on the performance of healthcare professionals. Continuous...